Numerical modeling of deformation and damage around underground excavation by phase-field method with hydromechanical coupling. (October 2021) - Yu, Zhan; Shao, Jianfu; Duveau, Gilles; Vu, Minh-Ngoc; Armand, Gilles
Abstract: In the context of feasibility study for geological disposal of radioactive waste, this work focuses on numerical modeling of hydromechanical response and induced damage zones around an experimental gallery at the underground research laboratory (URL) at Bure in France. A new phase-field method is first proposed by considering two independent damage fields in order to easily describe both tensile and shear cracks. The phase-field method is extended to saturated porous media by incorporating the effect of fluid pressure. The proposed method is implemented in a finite element code and applied to the experimental gallery. The evolutions of hydromechanical responses and induced damaged zones are analyzed in both excavation and post-excavation phases. Numerical results are compared with experimental observations and measurements. It is found that the proposed method is able to well describe the main features of hydromechanical responses and damage processes such as tensile and shear cracked zones.